High-entropy perovskite oxide doped ceramic and preparation method thereof
By introducing high-entropy perovskite oxide NBBSC into the Ca0.5Sr0.5TiO3 matrix to form a single solid solution, the problem of electronic conductivity behavior of ceramic capacitors under high electric fields was solved, realizing a ceramic material with high energy density and high energy storage efficiency.
Patent Information
- Application Number
- CN202512026369.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-30
- Publication Date
- 2026-01-27
- Estimated Expiration
- 2045-12-30
AI Technical Summary
Existing ceramic capacitors have difficulty maintaining a stable dielectric constant and enhancing breakdown strength while increasing energy density, which limits their application and development.
Introducing high-entropy perovskite oxide NBBSC into the Ca0.5Sr0.5TiO3 matrix to form a single solid solution improves dielectric properties and suppresses electronic conductivity by controlling the lattice distortion and disorder of the material.
It significantly improves the dielectric constant stability and breakdown field strength of ceramic materials, achieving high energy storage density and high energy storage efficiency, and possesses excellent dielectric properties and breakdown strength.
Smart Images

Figure CN121405461A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of high energy storage medium ceramics, and particularly relates to a high-entropy perovskite oxide doped ceramic and a preparation method thereof. BACKGROUND
[0002] Ceramic capacitors can realize instantaneous discharge due to their energy storage and release mechanism without chemical reaction. They have super-high power density, fast charging and discharging capacity, and high relative dielectric constant, and thus are favored in many promising applications. However, the further improvement of energy density and the enhancement of breakdown strength are mutually restricted. Therefore, it is of great significance to maintain stable dielectric constant and enhance breakdown strength for the application and development of ceramic capacitors.
[0003] Ca 0.5 Sr 0.5 TiO3ceramics, which have excellent linear dielectric properties and low capacitance-temperature change rate, have become a strong candidate for new generation of high-performance, lead-free, and high-reliability ceramic capacitors through their linear dielectric properties, high breakdown strength, and controllable modification strategies. The emerging material design theory of 'entropy engineering' can adjust the degree of lattice distortion and disorder within the material by controlling the configurational entropy, thus opening up a new path for creating ceramic materials with new structures and properties. The strong lattice distortion and high structural disorder inherent in high-entropy systems can bring unique properties such as high mechanical properties, high resistivity, and low thermal conductivity, which have potential major impact on the performance control and innovation of dielectric ceramics. Therefore, introducing new high-entropy perovskite oxides into linear Ca 0.5 Sr 0.5 TiO3ceramics, which have excellent linear dielectric properties and low capacitance-temperature change rate, have become a strong candidate for new generation of high-performance, lead-free, and high-reliability ceramic capacitors through their linear dielectric properties, high breakdown strength, and controllable modification strategies. The emerging material design theory of 'entropy engineering' can adjust the degree of lattice distortion and disorder within the material by controlling the configurational entropy, thus opening up a new path for creating ceramic materials with new structures and properties. The strong lattice distortion and high structural disorder inherent in high-entropy systems can bring unique properties such as high mechanical properties, high resistivity, and low thermal conductivity, which have potential major impact on the performance control and innovation of dielectric ceramics. Therefore, introducing new high-entropy perovskite oxides into linear Ca SUMMARY
[0004] The present application aims to provide a high-entropy perovskite oxide doped ceramic and a preparation method thereof, so that the ceramic capacitor has high energy density and excellent breakdown strength.
[0005] To achieve the above-mentioned purpose, the present application adopts the following technical solutions: A high-entropy perovskite oxide doped ceramic, whose stoichiometric formula is (1- x )Ca 0.5 Sr 0.5 TiO3- x NBBSC, wherein 0.05<= x <=0.2.
[0006] The preparation method of the high-entropy perovskite oxide doped ceramic comprises the following steps: Step 1, weigh, mix CaCO3, SrCO3 and TiO2 raw powders according to the molar mass percentage of Ca 0.5 Sr 0.5 TiO3 formula, to form mixed powder A; weigh, mix NaCO3, Bi2O3, BaCO3, SrCO3, CaCO3, TiO2 raw powders according to the molar mass percentage of NBBSC (i.e. Na 0.2 Bi 0.2 Ba 0.2 Sr 0.2 Ca 0.2 TiO3 formula, to form mixed powder B; Step 2, ball mill mixed powder A and mixed powder B respectively, and then dry and pre-burn the slurry after ball milling, to obtain Ca 0.5 Sr 0.5 TiO3 powder and NBBSC powder respectively; Step 3, mix Ca 0.5 Sr 0.5 TiO3 powder and NBBSC powder obtained in step 2 according to the molar mass percentage of (1- x )Ca 0.5 Sr 0.5 TiO3- x NBBSC (wherein, 0.05≤ x ≤0.2) formula, and then ball mill; dry and sieve the slurry after ball milling, to obtain mixed powder C; Step 4, press mixed powder C into a green body, and then sinter the green body, to obtain (1- x )Ca 0.5 Sr 0.5 TiO3- x NBBSC ceramic.
[0007] Further, each raw powder in step 1 is chemically pure or above.
[0008] Further, the ball milling process of mixed powder A in step 2 is as follows: the mass ratio of mixed powder A: zirconia ball stone: deionized water is 1:5:(1-1.2), the mass of the zirconia ball stone is proportioned according to the diameter of 10mm:6mm:3mm=5:3:1, the ball milling speed is 400rpm / min, and the ball milling time is 6-10h.
[0009] Further, the drying temperature of the slurry after ball milling of mixed powder A in step 2 is 80-100℃, and the drying time is 18-24h; the pre-burning temperature is 1150-1200℃, and the pre-burning time is 2-3h.
[0010] Further, the ball milling process of mixing powder B in step 2 is: the mass ratio of the mixed powder B: zirconia ball stone: deionized water is 1:5:(0.8-1.2), the mass of the zirconia ball stone is proportioned according to the diameter of 6mm:3mm=5:2, the ball milling speed is 400rpm / min, and the ball milling time is 8-10h. The mass ratio of the mixed powder B: zirconia ball stone: deionized water is 1:5:(0.8-1.2), the mass of the zirconia ball stone is proportioned according to the diameter of 6mm:3mm=5:2, the ball milling speed is 400rpm / min, and the ball milling time is 8-10h.
[0011] Further, the slurry drying temperature after ball milling of the mixed powder B in step 2 is 80-100℃, the drying time is 20-24h, the pre-sintering temperature is 900℃, and the pre-sintering time is 2-3h.
[0012] Further, the slurry drying temperature after ball milling of the mixed powder B in step 2 is 80-100℃, the drying time is 20-24h, the pre-sintering temperature is 900℃, and the pre-sintering time is 2-3h. 0.5 Sr 0.5 TiO3 powder and the NBBSC powder are mixed and then ball milled, and the process is: the mass ratio of the two mixed powders: zirconia ball stone: deionized water is 1:5:(0.8-1.2), the mass of the zirconia ball stone is proportioned according to the diameter of 6mm:3mm=5:2, the ball milling speed is 400rpm / min, and the ball milling time is 10-12h.
[0013] Further, the slurry drying temperature after ball milling of the mixed powder B in step 2 is 80-100℃, the drying time is 20-24h, the pre-sintering temperature is 900℃, and the pre-sintering time is 2-3h.
[0014] Further, the pressing in step 4 adopts a cold isostatic pressing mode, and the pressure is 100MPa.
[0015] Further, the sintering temperature in step 4 is 1380-1400℃, and the sintering time is 2-4h.
[0016] Compared with the prior art, the present application has the following beneficial technical effects: 1. The (1- x ) Ca 0.5 Sr 0.5 TiO3- x NBBSC ceramic material prepared by the method has the advantages that the high-entropy perovskite oxide NBBSC is introduced into the Ca 0.5 Sr 0.5 TiO3 matrix in a solid solution form to enter the crystal lattice of the Ca 0.5 Sr 0.5 TiO3 in a solid solution form, a single solid solution is formed, and the dielectric properties of the ceramic material are modified and improved, and the dielectric constant and dielectric loss of the ceramic material have good stability at different test frequencies.
[0017] 2. The (1- x ) Ca 0.5 Sr 0.5 TiO3- xThe NBBSC ceramic material inhibits the electron conduction behavior of the linear dielectric under high electric field by introducing the NBBSC system, and significantly improves the breakdown field strength of the ceramic system, so that the ceramic system has high energy storage density and high energy storage efficiency.
[0018] 3. The high-entropy perovskite oxide doped ceramic prepared by the method has excellent dielectric properties and breakdown field strength, high energy storage density and high energy storage efficiency, the preparation process is simple, the technical scheme is green and energy-saving, and therefore can be applied to fields with higher requirements for dielectric properties, such as high-energy storage dielectric ceramic capacitors, high-performance multilayer ceramic capacitors (MLCC), microwave communication devices, tunable devices, etc. BRIEF DESCRIPTION OF DRAWINGS
[0019] Figure 1 is each (1- x )Ca 0.5 Sr 0.5 TiO3- x XRD pattern of the NBBSC ceramic.
[0020] Figure 2 is each (1- x )Ca 0.5 Sr 0.5 TiO3- x Dielectric constant and dielectric loss of the NBBSC ceramic as a function of frequency.
[0021] Figure 3 is each (1- x )Ca 0.5 Sr 0.5 TiO3- x Energy storage density of the NBBSC ceramic. P - E DETAILED DESCRIPTION
[0022] The embodiments of the present application will be further described in detail below with reference to the accompanying drawings: The present application discloses a high-entropy perovskite oxide doped ceramic, which has a stoichiometric formula of (1- x )Ca 0.5 Sr 0.5 TiO3- x NBBSC, wherein 0.05≤ x ≤0.2. The present application introduces a high-entropy perovskite oxide NBBSC (i.e. Na 0.5 Sr 0.5 TiO3) into a linear dielectric Ca 0.2 Bi 0.2 Ba 0.2 Sr 0.2 Ca 0.2 TiO3), NBBSC enters Ca 0.5 Sr 0.5 TiO3lattice, forming a single solid solution, thereby modifying and improving the dielectric properties of the material; at the same time, the introduction of the NBBSC system suppresses the electron conduction behavior of the linear dielectric under high electric field, significantly improving the breakdown field strength of the ceramic system, thus making the ceramic system obtain high energy storage density and efficiency.
[0023] The specific preparation method of the high-entropy perovskite oxide doped ceramic is as follows: Step 1, weighing and batching, respectively obtaining mixed powder A and mixed powder B: CaCO3, SrCO3 and TiO2raw powder according to the molar mass percentage of Ca 0.5 Sr 0.5 TiO3formula, mixed to form mixed powder A; NaCO3, Bi2O3, BaCO3, SrCO3, CaCO3, TiO2raw powder according to the molar mass percentage of NBBSC (i.e. Na 0.2 Bi 0.2 Ba 0.2 Sr 0.2 Ca 0.2 TiO3formula, mixed to form mixed powder B. The above raw powder is chemically pure or above.
[0024] Step 2, ball milling, drying and pre-sintering of mixed powder A and mixed powder B respectively to obtain Ca 0.5 Sr 0.5 TiO3powder and NBBSC powder: Ball mill mixed powder A, the mass ratio of mixed powder A: zirconia ball stone: deionized water is 1:5:(1-1.2), the mass of the zirconia ball stone is proportioned according to the diameter of 10mm:6mm:3mm=5:3:1, the ball milling speed is 400rpm / min, the ball milling time is 6-10h, and the slurry after ball milling is dried at 80-100℃ for 18-24h, and the dried mixed powder A is pre-sintered at 1150-1200℃ for 2-3h to obtain the main crystal phase Ca 0.5 Sr 0.5 TiO3powder; Ball mill mixed powder B, the mass ratio of mixed powder B: zirconia ball stone: deionized water is 1:5:(0.8-1.2), the mass of the zirconia ball stone is proportioned according to the diameter of 6mm:3mm=5:2, the ball milling speed is 400rpm / min, the ball milling time is 8-10h, and the slurry after ball milling is dried at 80-100℃ for 20-24h, and the dried mixed powder B is pre-sintered at 900℃ for 2-3h to obtain NBBSC powder.
[0025] Step 3, weighing, mixing, ball milling, drying, and sieving to obtain mixed powder C: The Ca 0.5 Sr 0.5 TiO3 powder and the NBBSC powder are weighed and mixed according to the molar percentage of the chemical formula (1- x )Ca 0.5 Sr 0.5 TiO3- x NBBSC (wherein 0.05≤ x ≤0.2) and then ball milled; the mass ratio of the two mixed powders, zirconia ball stones, and deionized water is 1:5:(0.8-1.2), and the mass of the zirconia ball stones is proportioned according to the diameter 6mm:3mm=5:2; the ball milling speed is 400rpm / min, and the ball milling time is 10-12h; the slurry after ball milling is dried at 80-100℃ for 20-24h, and the dried product is sieved through a 120 mesh sieve to obtain the mixed powder C.
[0026] Step 4, pressing the green body and sintering the ceramic: The sieved mixed powder C is pressed into a green body by cold isostatic pressing, and the pressure is controlled at 100MPa; the prepared green body sample is placed in a sagger, preferably an alumina sagger, and a zirconia pad is laid at the bottom of the sagger; the sagger is placed in a high-temperature box furnace and sintered at 1380-1400℃ for 2-4h to obtain (1- x )Ca 0.5 Sr 0.5 TiO3- x NBBSC [i.e. (1- x )Ca 0.5 Sr 0.5 TiO3- x Na 0.2 Bi 0.2 Ba 0.2 Sr 0.2 Ca 0.2 TiO3] ceramic.
[0027] The above-mentioned raw materials are all commercially available.
[0028] The technical solutions of the present application are further described below through specific examples.
[0029] Example 1 x =0.05.
[0030] When ball milling mixed powder A, the mass ratio of mixed powder A:zirconia balls:deionized water is 1:5:1, the ball milling time is 6 hours, the slurry after ball milling is dried at 80℃ for 18 hours, and pre-calcined at 1150℃ for 2 hours to obtain the main crystalline phase Ca. 0.5 Sr 0.5 TiO3 powder.
[0031] When ball milling mixed powder B, the mass ratio of mixed powder B:zirconia balls:deionized water is 1:5:0.8, the ball milling time is 8h, the slurry after ball milling is dried at 80℃ for 20h, and pre-calcined at 900℃ for 3h to obtain NBBSC powder.
[0032] Ball mill Ca 0.5 Sr 0.5 When TiO3 and NBBSC are mixed into powder, the mass ratio of the two mixed powders, zirconium oxide balls and deionized water, is 1:5:1. The ball milling time is 10 hours. After ball milling, the slurry is dried at 80°C for 20 hours to obtain mixed powder C.
[0033] During sintering, the sintering temperature was 1400℃, and the holding time was 2 hours, yielding 0.95Ca. 0.5 Sr 0.5 TiO3-0.05NBBSC ceramic.
[0034] Example 2 x =0.10.
[0035] When ball milling mixed powder A, the mass ratio of mixed powder A:zirconia balls:deionized water is 1:5:1, the ball milling time is 8 hours, the slurry after ball milling is dried at 90℃ for 20 hours, and pre-calcined at 1200℃ for 2.5 hours to obtain the main crystalline phase Ca. 0.5 Sr 0.5 TiO3 powder.
[0036] When ball milling mixed powder B, the mass ratio of mixed powder B:zirconia balls:deionized water is 1:5:1, the ball milling time is 10h, the slurry after ball milling is dried at 90℃ for 20h, and pre-calcined at 900℃ for 2.5h to obtain NBBSC powder.
[0037] Ball mill Ca 0.5 Sr 0.5 When TiO3 and NBBSC are mixed into powder, the mass ratio of the two mixed powders, zirconium oxide balls and deionized water, is 1:5:0.8. The ball milling time is 12 hours, and the slurry after ball milling is dried at 90°C for 20 hours to obtain mixed powder C.
[0038] During sintering, the sintering temperature was 1390℃, and the holding time was 3.5h, yielding 0.9Ca. 0.5 Sr 0.5 TiO3-0.1NBBSC ceramics.
[0039] Example 3 x =0.15.
[0040] When ball milling mixed powder A, the mass ratio of mixed powder A:zirconia balls:deionized water is 1:5:1.1, and the ball milling time is 10 hours. After ball milling, the slurry is dried at 100℃ for 22 hours and pre-calcined at 1175℃ for 3 hours to obtain the main crystalline phase Ca. 0.5 Sr 0.5 TiO3 powder.
[0041] When ball milling mixed powder B, the mass ratio of mixed powder B:zirconia balls:deionized water is 1:5:1.1, the ball milling time is 10h, the slurry after ball milling is dried at 100℃ for 22h, and pre-calcined at 900℃ for 2.5h to obtain NBBSC powder.
[0042] Ball mill Ca 0.5 Sr 0.5 When TiO3 and NBBSC are mixed into powder, the mass ratio of the two mixed powders, zirconium oxide balls and deionized water, is 1:5:1.1. The ball milling time is 12 hours. After ball milling, the slurry is dried at 100°C for 22 hours to obtain mixed powder C.
[0043] During sintering, the sintering temperature was 1390℃, and the holding time was 4 hours, yielding 0.85Ca. 0.5 Sr 0.5 TiO3-0.15NBBSC ceramics.
[0044] Example 4 x =0.20.
[0045] When ball milling mixed powder A, the mass ratio of mixed powder A:zirconia balls:deionized water is 1:5:1.2, the ball milling time is 9 hours, the slurry after ball milling is dried at 100℃ for 24 hours, and pre-calcined at 1200℃ for 3 hours to obtain the main crystalline phase Ca. 0.5 Sr 0.5 TiO3 powder.
[0046] When ball milling mixed powder B, the mass ratio of mixed powder B:zirconia balls:deionized water is 1:5:1.2, the ball milling time is 9h, the slurry after ball milling is dried at 100℃ for 24h, and pre-calcined at 900℃ for 2h to obtain NBBSC powder.
[0047] Ball mill Ca 0.5 Sr 0.5 When TiO3 and NBBSC are mixed into powder, the mass ratio of the two mixed powders (zirconia balls and deionized water) is 1:5:1.2, the ball milling time is 11 h, and the slurry after ball milling is dried at 100℃ for 24 h to obtain mixed powder C.
[0048] During sintering, the sintering temperature was 1380℃, and the holding time was 3 hours, yielding 0.8Ca. 0.5 Sr 0.5 TiO3-0.2NBBSC ceramics.
[0049] The high-entropy perovskite oxide-doped ceramics prepared in Examples 1-4 were subjected to xRD analysis, and the results were obtained. Figure 1 of (1- x )Ca 0.5 Sr 0.5 TiO3- x NBBSC (0.05≤ x XRD pattern of ceramics ≤0.2). From Figure 1 It can be seen that all ceramic samples exhibit a typical single ABO3 type perovskite structure, indicating that NBBSC enters Ca in a solid solution form. 0.5 Sr 0.5 The TiO3 lattice forms a single solid solution. NBBSC does not exist as a second phase, but is completely integrated into Ca in a solid solution form. 0.5 Sr 0.5 The TiO3 lattice forms a single, homogeneous perovskite solid solution. This single solid solution structure avoids the adverse effects of multiphase interfaces (such as interface defects and stress concentration), ensuring the structural consistency and performance controllability of the material.
[0050] The dielectric properties of the high-entropy perovskite oxide-doped ceramics prepared in Examples 1-4 were tested with respect to frequency variations, and the results were obtained. Figure 2 of (1- x )Ca 0.5 Sr 0.5 TiO3- x NBBSC (0.05≤ x ≤0.2) Ceramic dielectric constant and dielectric loss as a function of frequency. From Figure 2 It can be seen that the dielectric constant and dielectric loss of the ceramic material have good stability at different test frequencies, especially the dielectric constant remains basically unchanged at different frequencies; and it can also be seen that the dielectric constant of the ceramic material gradually increases with the increase of the content of high-entropy perovskite oxide NBBSC.
[0051] The energy storage performance of the high-entropy perovskite oxide-doped ceramics prepared in Examples 1-4 was tested, and the results were obtained. Figure 3 of (1- x )Ca 0.5 Sr 0.5 TiO3- x NBBSC (0.05≤ x ≤0.2) system ceramics P- E The atlas is obtained by calculating the data. Figure 3 Through the calculation of the data, all ceramic system samples have high energy storage density, and high energy storage efficiency (all greater than 96%) is obtained, especially when x =0.15, the 0.85Ca 0.5 Sr 0.5 TiO3-0.15NBBSC system ceramic obtains very high energy storage density (4.37J / cm 3 ); at the same time, all ceramic samples have high breakdown field strength (330-560kV / cm), especially when x =0.15, the 0.85Ca 0.5 Sr 0.5 TiO3-0.15NBBSC system ceramic has a breakdown field strength of 560kV / cm. It can be seen that the introduction of the NBBSC system suppresses the electron conduction behavior of the linear dielectric under high electric field, significantly improves the breakdown field strength of the ceramic system, and thus makes the ceramic system obtain high energy storage density and high energy storage efficiency.
[0052] The high-entropy perovskite oxide doped ceramic prepared by the application has good stability of dielectric constant and dielectric loss under different test frequencies, the breakdown field strength is significantly improved, and has high energy storage density and high energy storage efficiency; the preparation process is simple, and the formula is a lead-free material, the sintering of the ceramic is carried out in an air atmosphere, and no special atmosphere is needed, so the technical scheme is green and energy-saving, and therefore can be applied to fields with higher requirements for dielectric properties, such as high-energy storage dielectric ceramic capacitors, high-performance multilayer ceramic capacitors (MLCC), microwave communication devices, tunable devices, etc.
[0053] The above is only the preferred specific embodiment of the application, but the protection scope of the application is not limited thereto, any person skilled in the art can easily think of changes or replacements within the technical range disclosed by the application, which should be covered within the protection scope of the application. Therefore, the protection scope of the application should be subject to the protection scope of the claims.
Claims
1. A high-entropy perovskite oxide-doped ceramic, characterized in that, Its stoichiometric formula is (1- x )Ca 0.5 Sr 0.5 TiO3- x NBBSC, where 0.05≤ x ≤0.
2.
2. The method for preparing high-entropy perovskite oxide-doped ceramics according to claim 1, characterized in that, Includes the following steps: Step 1, mix the raw CaCO3, SrCO3 and TiO2 powders according to Ca 0.5 Sr 0.5 Weigh and mix the TiO3 chemical formula according to the molar mass percentage to form mixed powder A; weigh and mix the original powders of NaCO3, Bi2O3, BaCO3, SrCO3, CaCO3, and TiO2 according to the molar mass percentage of the NBBSC chemical formula to form mixed powder B. Step 2: Mixed powder A and mixed powder B are ball-milled separately. The ball-milled slurry is then dried and pre-calcined to obtain Ca. 0.5 Sr 0.5 TiO3 powder and NBBSC powder; Step 3, Ca 0.5 Sr 0.5 TiO3 powder and NBBSC powder, according to (1- x )Ca 0.5 Sr 0.5 TiO3- x NBBSC (where 0.05≤ x ≤0.2) Weigh and mix the chemical formula by molar mass percentage, then ball mill; after ball milling, dry the slurry and sieve to obtain mixed powder C; Step 4: Press the mixed powder C into a green body, and sinter the green body to obtain (1- x )Ca 0.5 Sr 0.5 TiO3- x NBBSC ceramics.
3. The method for preparing high-entropy perovskite oxide-doped ceramics according to claim 2, characterized in that, The raw powders mentioned in step 1 are of chemical purity or higher.
4. The method for preparing high-entropy perovskite oxide-doped ceramics according to claim 2, characterized in that, The ball milling process of mixed powder A in step 2 is as follows: the mass ratio of mixed powder A: zirconia balls: deionized water is 1:5:(1-1.2), the mass of the zirconia balls is proportioned according to the diameter ratio of 10mm:6mm:3mm=5:3:1, the ball milling speed is 400rpm / min, and the ball milling time is 6-10h.
5. The method for preparing high-entropy perovskite oxide-doped ceramics according to claim 2, characterized in that, In step 2, the drying temperature of the slurry after ball milling of mixed powder A is 80-100℃ and the drying time is 18-24h; the pre-calcination temperature is 1150-1200℃ and the pre-calcination time is 2-3h.
6. The method for preparing high-entropy perovskite oxide-doped ceramics according to claim 2, characterized in that, The ball milling process of mixed powder B in step 2 is as follows: the mass ratio of mixed powder B: zirconia balls: deionized water is 1:5:(0.8-1.2), the mass of the zirconia balls is proportioned according to a diameter ratio of 6mm:3mm=5:2, the ball milling speed is 400rpm / min, and the ball milling time is 8-10h.
7. The method for preparing high-entropy perovskite oxide-doped ceramics according to claim 2, characterized in that, In step 2, the slurry after ball milling of mixed powder B is dried at a temperature of 80-100℃ for 20-24 hours; the pre-calcination temperature is 900℃ for 2-3 hours.
8. The method for preparing high-entropy perovskite oxide-doped ceramics according to claim 2, characterized in that, In step 3, Ca 0.5 Sr 0.5 The process of ball milling TiO3 powder and NBBSC powder is as follows: the mass ratio of the two mixed powders, zirconia balls and deionized water, is 1:5:(0.8-1.2). The mass of the zirconia balls is proportioned according to a diameter ratio of 6mm:3mm=5:
2. The ball milling speed is 400rpm / min and the ball milling time is 10-12h.
9. The method for preparing high-entropy perovskite oxide-doped ceramics according to claim 2, characterized in that, In step 3, the slurry after ball milling is dried at a temperature of 80-100℃ for 20-24 hours; a 120-mesh sieve is used for sieving.
10. The method for preparing high-entropy perovskite oxide-doped ceramics according to claim 2, characterized in that, In step 4, cold isostatic pressing is used, with a pressure of 100 MPa, a sintering temperature of 1380-1400℃, and a sintering time of 2-4 hours.
Citation Information
Patent Citations
High-energy-storage non-equimolar-ratio high-entropy perovskite oxide ceramic material and preparation method thereof
CN114085079A
Barium strontium titanate-based high-entropy energy storage ceramic with core-shell structure and preparation method of barium strontium titanate-based high-entropy energy storage ceramic
CN119504256A
High-entropy relaxation type lead-free perovskite ceramic and preparation method thereof
CN120682032A
Dielectric porcelain composition and electronic component using the same
JP2001130955A
Ten-membered fergusonite structure high-entropy oxide ceramic and preparation method thereof
US11673839B1